High genetic variability in Taenia multiceps larvae: A mitochondrial DNA-based study of sheep isolates using CO1 and NADH1 genes - Celik, Figen; Uslug, Muhammet; Tekin, Afra Sena; Simsek, Sami (Elsevier Sci Ltd, 2025)
Coenurus cerebralis, the larval stage of Taenia multiceps, is a significant parasitic threat to small ruminants, yet its molecular diversity remains underexplored in many endemic regions. This study investigated the genetic variability of C. cerebralis from sheep in Elazig province, T & uuml;rkiye, by analyzing mitochondrial CO1 (812 bp) and NADH1 (498 bp) gene regions. Sequence data from 39 isolates confirmed the presence of T. multiceps, with 21 CO1 and 17 NADH1 haplotypes identified over half of which were singletons. Most polymorphic sites were parsimony-informative, indicating meaningful evolutionary divergence within the population. Neutrality tests (Tajima's D and Fu's Fs) suggested signals of population expansion or selection pressure. Phylogenetic analyses confirmed the genetic distinctiveness of the isolates and revealed higher diversity than previously documented in T & uuml;rkiye. The observed haplotype diversity, coupled with low nucleotide diversity, reflects recent diversification events within the parasite population. These findings highlight ongoing microevolutionary processes in C. cerebralis and underscore the need for region-specific molecular surveillance and targeted control measures. Enhanced understanding of genetic variation in C. cerebralis is critical for improving diagnostic strategies, informing regional epidemiological models, and designing effective intervention programs against coenurosis in endemic areas.
Keywords: Coenurus cerebralis; Sheep; CO1; NADH1; Haplotype; T & uuml;rkiye